Building a republican nation in Vietnam, 1920-1963 - Tran, Nu-Anh; Vu, Tuong, 1965- (Studies of the Weatherhead East Asian Institute, Columbia University., 2023)
Western observers have long considered communism to be synonymous with Vietnam's modern historical experience. Eager to make sense of the North Vietnamese victory in the Vietnam War, scholars and journalists have spilled much ink on the history of Vietnamese communists. But this preoccupation has obscured the diversity of ideas and experiences that defined Vietnam in the twentieth century, in which communism represented just one of many tendencies. Building a Republican Nation in Postcolonial Vietnam, 1920-1963, posits that republicanism shaped modern Vietnam no less profoundly than communism. Republicans championed representative government, the universal rights of man, civil liberties, and the primacy of the nation. These ideas infused the thinking of Vietnamese reformers, dissidents, and revolutionaries from the 1900s onward, including many men and women who went on to lead the struggle for independence. Republicanism was also one of the chief inspirations for the establishment of the Republic of Vietnam (also known as South Vietnam) in 1955.This interdisciplinary volume brings together eleven essays by historians, political scientists, literary scholars, and sociologists, who make use of fresh sources to study the development of republicanism from the colonial period to the First Republic of Vietnam (1955-1963). The introduction by coeditors Nu-Anh Tran and Tuong Vu critically analyzes the existing scholarship on the First Republic, explains how the concept of republicanism can illuminate developments in the Saigon-based state, and situates the regime in a comparative context with South Korea. Peter Zinoman's chapter reviews the historiography on republicanism and modern Vietnam and heralds the arrival of the "republican moment" in the field of Vietnam studies. Several chapters by Nguyễn Lương Hải Khôi, Martina Thucnhi Nguyen, and Yen Vu examine the transformation of republican ideas. Nu-Anh Tran and Duy Lap Nguyen explore competing concepts of democracy and the factional politics of the First Republic. The essays by Jason Picard, Cindy Nguyen, Hoàng Phong Tuấn, Nguyễn Thị Minh, and Y Thien Nguyen analyze nation- and state-building efforts in the 1950s and 1960s. Collectively, the essays give voice to Vietnamese republicans, from the ideas they espoused to the institutions they built and the legacies they left behind.